Sosialisasi Pemilihan Karir di Sekolah Menengah Atas (SMA) Negeri 01 Reteh - Rika Devianti; Mardiah Mardiah; Dina Liana; Martina Napratilora; Faridatul Munawaroh; Hendro Lisa (ABDIMASY: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
Career selection is an important thing that needs to be considered by students in adjusting their talents, interests or abilities with the career to be chosen. However, in reality, there are still cases of mismatch of talents, interests/ability with the chosen career, causing individuals to become stressed, burdened and even drop out of college. Thus, the need for socialization of career selection in order to direct individuals to achieve success in the future. This service is carried out at the State High School (SMA) 01 Reteh. This type of research is community service with the lecture method, and question and answer. The steps carried out in this service are in the form of providing information about education or position, student achievement, and evaluation. The results of this service are students' understanding related to career choice, it can be seen that they can adjust the choice of majors according to their talents, interests and aspirations.